Euglossa paisa, a new species of orchid bee from the Colombian Andes (Hymenoptera: Apidae) - Ramírez, Santiago (Zootaxa, 2005)
A distinct new species of orchid bee, Euglossa paisa Ramírez n. sp., is here described. Various morphological characters suggest that this new taxon belongs to the subgenus Glossurella, a group composed of 21 species whose members occur throughout low and mid elevation tropical America. E. paisa n. sp. is morphologically closest to E. oleolucens Dressler, a species endemic to the montane region of southern Costa Rica, and these two to E. fuscifrons Dressler, a species endemic to the lowland wet forests of the northwest Amazon Basin. E. paisa is endemic to the Cordillera Central of Colombia, a region of elevated diversity and profuse endemism.